1989
DOI: 10.1148/radiology.171.2.2649925
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Doppler US of the kidney: differentiation of obstructive from nonobstructive dilatation.

Abstract: Distinction of the obstructed from the nonobstructed dilated renal collecting system is a difficult problem often requiring interventional procedures and pressure measurements. The authors prospectively performed duplex Doppler ultrasound (US) evaluations in 21 kidneys (obstructed, n = 14; nonobstructed, n = 7) immediately before percutaneous nephrostomy. In addition, ten of the obstructed kidneys were evaluated with follow-up Doppler US after percutaneous nephrostomy. Renal obstruction caused a change in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(119 citation statements)
references
References 0 publications
3
111
1
3
Order By: Relevance
“…Previous studies showed that the RI of hydronephrotic obstructed kidneys is significantly higher than that in kidneys with unobstructive pelvicalyceal dilatation [1]. A high intrarenal RI in obstructed kidneys is mainly a result of the decrease in diastolic renal blood flow velocity.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies showed that the RI of hydronephrotic obstructed kidneys is significantly higher than that in kidneys with unobstructive pelvicalyceal dilatation [1]. A high intrarenal RI in obstructed kidneys is mainly a result of the decrease in diastolic renal blood flow velocity.…”
Section: Discussionmentioning
confidence: 92%
“…A high intrarenal RI in obstructed kidneys is mainly a result of the decrease in diastolic renal blood flow velocity. Platt et al [1] reported that the RI in normal adult humans is f0.7; using this value, Doppler US has clinically excellent sensitivity and specificity in determining the presence or absence of obstruction in patients with calyceal dilatation. However, there are cases of mild ureteric obstruction with an intrarenal RI of f0.70 [2] and the present UPUO dog model closely represents such chronic mild unilateral ureteric obstruction in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A better and direct functional evidence of the obstruction is obtained by the more recent Doppler US techniques to gather more information on the level of obstruction. 14,15 The response of the renal blood flow to the site of urinary obstruction is said to be phasic. [16][17][18][19] At the onset of the obstruction, there is an immediate increase in the renal pelvic pressure, which results in the vasodilatation caused by the vasoconstrictor factors.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is a possible bacterial infection of the scarred renal tissues and functional tubule abnormalities in conjunction with the compromised immunity, leading to abscess formation [26,27] Table(3) presented the lungs CT manifestation in SCA : pleural effusion, pneumonia ,atelectasis, ground glass nodules ,consolidation ,fibrosis lung abscess which was found in different ages as well; at all types of SCD including Hb SS ,Hb SC ,Hb SB 0-thalassemia ,Hb SB+ thalassemia that are presented in table ( 8) Similar studies have mentioned that the acute chest syndrome is one of the most common causes of hospitalization and even death of SCA patients, pulmonary vascular obstruction. [28]and pleural effusion may also be seen, [29,30] Patients with SCA may develop obstructive or restrictive lung diseases, when there is a progressive decline in the pulmonary functions .This may be explained by established fibrotic lung changes from repeated episodes of pulmonary infective and vaso-occlusive events. High resolution CT scan (HRCT) shows these interstitial changes, that are of reticular or reticulonodular pattern and may be associated with traction bronchiectasis [31] …”
Section: Discussionmentioning
confidence: 99%